PERANCANGAN PROGRAM APLIKASI INFORMASI FOTO, VIDEO, DAN AUDIO BERBASIS WEB - Surono Surono; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Making the design of the application program information, videos, and audio on web-based social research is to help the IS-STS Lab researchers manage data storage for photos, videos, and audio, as well as helping to facilitate the search image data, video, and audio on research . The methodology used in the manufacture of these applications using SDLC (Systems development life cycle) is the method comprising the steps of planning, analysis phase, design phase and the implementation phase. This application program design used a helper application such as Microsoft Word to create reports, Microsoft Visio flowchart to make the design as, Data Flow Diagrams (DFD), Entity Relation Diagram (ERD), interrelated table, My Structured Query Language (MYSQL) as database, and Page Hypertext Preprocessor (PHP) as a programming language. The application program has been tested using Black box testing methods and testing User Acceptance Test (UAT). Result of making this application program can help researchers in the IS-STS Lab in managing image data storage, video and audio, help in creating reports, and assist in the search image data, video, and audio are already in the store. Key wordsLab IS-STS, Application program,  data